Essentials of discursive psychology - McMullen, Linda M. (Essentials of qualitative methods, 2021)
"The brief, practical texts in the Essentials of Qualitative Methods series introduce social science and psychology researchers to key approaches to capturing phenomena not easily measured quantitatively, offering exciting, nimble opportunities to gather in-depth qualitative data. In this step-by-step guide to conducting a research study, Linda McMullen describes the innovative ways in which discursive psychology analyzes language at both the micro and macro levels. Discursive psychologists reconceptualize talk and text as being situated in a social context, rather than thinking of talk as a route to our thoughts. For example, this approach could be used to study how people use arguments for and against the notion of human-induced climate change, or how they criticize each other in face-to-face encounters. About the Essentials of Qualitative Methods book series: Even for experienced researchers, selecting and correctly applying the right method can be challenging. In this groundbreaking series, leading experts in qualitative methods provide clear, crisp, and comprehensive descriptions of their approach, including its methodological integrity, and its benefits and limitations. Each book includes numerous examples to enable readers to quickly and thoroughly grasp how to leverage these valuable methods"--Provided by publisher.